Application and Progress of Supercritical CO₂ Extraction in Metal Recovery - Rozanski, Robert; Teang, Marie; Dau, Halena (Journal of Functional Materials and Applied Engineering, 2026)
In the context of increasingly scarce resources and prominent environmental issues, typical metal-containing waste materials (such as nuclear waste, uranium tailings, spent catalysts, and spent batteries) are rich in valuable metals, including lanthanides, actinides, and transition metals. Recycling these metals is significant for both resource recovery and environmental protection. Supercritical carbon dioxide (scCO₂) extraction technology is a novel and environmentally friendly method characterized by its green and efficient nature. In this paper, an overview of the application of scCO₂ extraction technology for the recovery of metals from waste is presented, and research trends are summarized. The efficiency of metal recovery based on scCO₂ has been significantly improved, with the extraction rate of some valuable metals reaching over 90%. CiteSpace software was used to visualize the research status of metal recovery using scCO₂ extraction technology. Moreover, suggestions are proposed for future development in the field of metal recycling.